2023
DOI: 10.1038/s41398-023-02599-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual cases of major adolescent psychiatric conditions with artificial intelligence

Nina de Lacy,
Michael J. Ramshaw,
Elizabeth McCauley
et al.

Abstract: Three-quarters of lifetime mental illness occurs by the age of 24, but relatively little is known about how to robustly identify youth at risk to target intervention efforts known to improve outcomes. Barriers to knowledge have included obtaining robust predictions while simultaneously analyzing large numbers of different types of candidate predictors. In a new, large, transdiagnostic youth sample and multidomain high-dimension data, we used 160 candidate predictors encompassing neural, prenatal, developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In this context the PTMF may be helpful in eliciting adverse experiences that were previously obscured. As there is a growing body of evidence that suggests that difficult lives explain depression better than broken brains ( 61 , 62 ), treatment approaches that acknowledge this can potentially be more effective than interventions that primarily deal with downstream symptoms. One implication of our findings on the relevance of negative operations of power in the context of depression is that intersectional analyses of these mechanisms may be useful, both to enable individual empowerment, restored self-confidence and better life navigation skills as part of depression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this context the PTMF may be helpful in eliciting adverse experiences that were previously obscured. As there is a growing body of evidence that suggests that difficult lives explain depression better than broken brains ( 61 , 62 ), treatment approaches that acknowledge this can potentially be more effective than interventions that primarily deal with downstream symptoms. One implication of our findings on the relevance of negative operations of power in the context of depression is that intersectional analyses of these mechanisms may be useful, both to enable individual empowerment, restored self-confidence and better life navigation skills as part of depression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both neural network model and decision tree model have higher predictability and are better than linear regression model. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both neural network model and decision tree model have higher predictability and are better than linear regression model. 7 However, the variables studied in the medical field are more objective measurements, while in the field of psychology, they are more subjective variables. In addition, in the field of psychology, such as junior high school students' questionable Internet use and adolescent mental health problems, 8 it is easy to be affected by many variables, such as individual characteristics, school, family, environment and so on.…”
Section: Introductionmentioning
confidence: 99%